1987
DOI: 10.1016/0035-9203(87)90299-9
|View full text |Cite
|
Sign up to set email alerts
|

Semen analyses in Hansen's disease

Abstract: Disturbances in semen quality can be induced by exogenous factors including trivial illnesses like throat infection and viral infection with fever. Hansen's disease presents with problems such as long term dependence on drugs, hyperthermia, haemolysis and anxiety due to social stigma. In the present study the semen quality of patients with tuberculoid-type leprosy was studied during and after withdrawal of therapy. Patients generally had low sperm counts and spermatozoal motility was low with a greater number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…There are at least three possible speculations on how the SARS-CoV-2 virus can affect testicular functions and sperm quality: (1) body fever contributes to an increase in testicular temperature which may cause poor sperm quality, this notion has been generally accepted. Several authors showed a negative influence of fever on semen quality with impaired sperm density, progressive motility, and morphology occurring a few weeks after the onset of fever and lasting for 1–3 months [ 20 , 21 , 23 , 58 60 , 82 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are at least three possible speculations on how the SARS-CoV-2 virus can affect testicular functions and sperm quality: (1) body fever contributes to an increase in testicular temperature which may cause poor sperm quality, this notion has been generally accepted. Several authors showed a negative influence of fever on semen quality with impaired sperm density, progressive motility, and morphology occurring a few weeks after the onset of fever and lasting for 1–3 months [ 20 , 21 , 23 , 58 60 , 82 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In case reports or small retrospective series of patients, several authors (MacLeod, 1951; Kar, 1953; French et al. , 1973; Koentjoro‐Soehadi, 1982; Sheriff, 1987; Schill, 1994; Evenson et al. , 2000; Jung et al.…”
Section: Lifestylementioning
confidence: 99%
“…Research articles on humans published in English from 1965 to 2015 were included in this report [23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1). .…”
Section: Data Extraction and Data Anaysismentioning
confidence: 99%